2016
DOI: 10.1308/rcsann.2016.0040
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation in major trauma admissions

Abstract: INTRODUCTION Trauma is a significant cause of morbidity and mortality in the UK. Since the inception of the trauma networks, little is known of the temporal pattern of trauma admissions. METHODS Trauma Audit and Research Network data for 1 April 2011 to 31 March 2013 were collated from two large major trauma centres (MTCs) in the South East of England: Brighton and Sussex University Hospitals NHS Trust (BSUH) and St George's University Hospitals NHS Foundation Trust (SGU). The number of admissions and the inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…Studies on trauma populations describe trends towards increased admissions associated with warmer weather and summer months (northern temperate zone) (Kieffer et al 2016 ; Ali and Willett 2015 ; Rising et al 2006 ; Roislien et al 2018 ; Bjarkø et al 2019 ). However, our study did not identify significant variations between monthly admissions or TBI severity during the five-year period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on trauma populations describe trends towards increased admissions associated with warmer weather and summer months (northern temperate zone) (Kieffer et al 2016 ; Ali and Willett 2015 ; Rising et al 2006 ; Roislien et al 2018 ; Bjarkø et al 2019 ). However, our study did not identify significant variations between monthly admissions or TBI severity during the five-year period.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, for in hospital resource planning accurate information on patient load, patient characteristics, injury severity and time of admittance is of great importance. Several studies have shown the number of admissions for trauma patients increases on weekends, in the evenings, and are subject to seasonal variation (Kieffer et al 2016 ; Robertson and Giannoudis 2004 ; Stonko et al 2018 ; Vaziri et al 2007 ; Ali and Willett 2015 ; Rising et al 2006 ; Roislien et al 2018 ). We wanted to study the extent this is applicable to TBI patients.…”
Section: Introductionmentioning
confidence: 99%
“…Studies exploring seasonal effects tend to treat months and years as separate units in time [ 3 , 7 , 8 , 27 ]. The observed long-term non-linear increase in daily number of trauma admissions in this study underpins that using months as the unit of analysis cannot automatically be recommended, as this will effectively imply turning continuous time into a categorical variable, potentially masking clinically valuable information.…”
Section: Discussionmentioning
confidence: 99%
“…Much like all medical and surgical specialties, there has been an anecdotal drop number of trauma calls per day, and the number of in‐patient admissions to our major trauma centre, one of the busiest in the United Kingdom. Previously, published literature from the UK has demonstrated significant seasonal variation in trauma admissions 6 . However, the impact of the pandemic, coupled with social isolation, on trauma admissions and the delivery of trauma care is not known.…”
mentioning
confidence: 99%